Increase in Growth N, P, and K Absorption and Production of Corn (Zea mays L.) on Rainfed Paddy Fields Through Application of NPK 16-16-16 Fertilizer - Chosa Zahro Fatiha; Retno Suntari; Ratna Eka Sari Putri (Universitas Islam Raden Rahmat, Malang, 2025)
One of the national strategic foodstuffs is maize, whose production can still be increased because the actual yield in the lower than the potential yield. Problems that often arise is low fertility, especially nutrients N, P, and K. The aims of this research is to know the effect of NPK 16:16:16 fertilizer application on the growth, production and uptake of corn plants. The research was conducted in Mojokerto rainfed paddy fields with a randomized group design. The treatments given are 8 in the form of different doses of NPK 16:16:16 fertilizer and control in the form of no fertilizer and NPK 15:15:15 according to the recommended dose. Observation parameters observed were soil analysis, number of leaves, plant height, plant dry weight, NPK nutrient uptake and weight of 100 grains. Data analysis used ANOVA f test at 5% level and DMRT further test at 5% level. The application of NPK 16-16-16 fertilizer at 1/4 dose significantly increased the growth of corn plant and nutrient uptake. NPK 16:16:16 fertilizer at 1/2 dose significantly increased production.